Chitosan-Based Nanoparticles with Optimized Parameters for Targeted Delivery of a Specific Anticancer Drug-A Comprehensive Review - Joanna Kurczewska (MDPI AG, 2023)
Chitosan is a positively charged polysaccharide obtained through chitin deacetylation. It belongs to a group of biodegradable, bioavailable, and non-toxic materials of natural origin; thus, it is a promising matrix for creating delivery systems of different active agents. Recently, much attention has been paid to nanodelivery systems as carriers to enable better bioavailability, and thus higher efficiency of the loaded drug. The present review is focused on the progress in chitosan-based nanoparticles for the targeted delivery of antitumor drugs. The paper discusses literature reports from the last three years in which chitosan nanoparticles were applied as carriers for active substances used in antitumor therapy and potential new drugs with anticancer properties. Special attention was paid to the different treatments applied to increase the therapeutic effectiveness and minimize the side effects of a specific active substance.